Control of Delegated Legislation in Nigeria: a myth or a reality? - Kingsley Osinachi N. Onu (LEGAL BRIEF, 2022)
It is a common saying that power corrupts and absolute power corrupts absolutely, so is the case with delegated legislation. The legislature sometimes delegates its law making power(s) statutorily to the other arms of governments/institutions or persons to aid ease of governance. The delegate, therefore, handles the deals of the power delegated with a touch of expertise and skill. This paper uses an armchair research approach to examine the control of delegated legislation in Nigeria. The paper finds that there is a challenge of control of delegated legislation in Nigeria due to the absence of a formal law on rule making like the Statutory Instruments Act, 1946 of England. It concludes by recommending that a law be enacted which will detail the guideline for making delegated legislation with strict provisions on scrutiny by the legislature or its committee.